1993
DOI: 10.1093/cvr/27.10.1790
|View full text |Cite
|
Sign up to set email alerts
|

On the involvement of a cyclosporin A sensitive mitochondrial pore in myocardial reperfusion injury

Abstract: Mammalian cardiomyocytes may withstand prolonged periods of ischaemia, only to die on reperfusion. We review data that implicate mitochondrial dysfunction as a basis for reperfusion induced cell injury, and present some new evidence that suggests that such a mechanism operates in intact cardiomyocytes. The mitochondrial dysfunction is the consequence of the opening of high conductance pores in the inner mitochondrial membrane, which uncouple mitochondrial oxidative phosphorylation, promoting ATP hydrolysis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
154
3
5

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(167 citation statements)
references
References 0 publications
5
154
3
5
Order By: Relevance
“…4A and 5, A and B). Previously, it has been shown that a 12% change in fluorescence signal of JC-1 reflects a 10-mV change in the membrane potential (41). Therefore, the increases in JC-1 fluorescence at 12, 18, and 24 h of cisplatin exposure in RPTC correspond to ⌬⌿ m of Ϫ180, Ϫ230, and Ϫ270 mV, respectively.…”
Section: Resultsmentioning
confidence: 86%
“…4A and 5, A and B). Previously, it has been shown that a 12% change in fluorescence signal of JC-1 reflects a 10-mV change in the membrane potential (41). Therefore, the increases in JC-1 fluorescence at 12, 18, and 24 h of cisplatin exposure in RPTC correspond to ⌬⌿ m of Ϫ180, Ϫ230, and Ϫ270 mV, respectively.…”
Section: Resultsmentioning
confidence: 86%
“…5C; Schinder et al 1996;Nieminen et al 1996;Castilho et al 1998;Keelan et al 1998). A similar process may take place in the heart following reperfusion after an ischaemic episodeagain conditions in which mitochondrial Ca¥ loading will be combined with oxidative stress, leading to MPT and cell death (Duchen et al 1993a;Griffiths & Halestrap, 1995). Why should the cell place such fundamental decisions about life and death in the hands of the mitochondrial interlopers?…”
Section: Modulation Of Spatiotemporal [Ca¥]c Signals By Mitochondriamentioning
confidence: 99%
“…Mitochondrial dysfunction due to a permeability transition can precipitate a bioenergetic crisis with ATP depletion and Ca 2ϩ dysregulation (2)(3)(4). On the other hand, mitochondria can release proteins that cause cell death through both caspase-dependent and caspase-independent mechanisms (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%